Geo CPS: spatial challenges and opportunities for CPS in the geographic dimension - Wanglin Yan; Takeo Sakairi (Journal of Urban Management, 2019)
Recent advances in the Internet of Things (IoT) have brought great opportunities for geographical information systems (GIS) to be integrated with cyber-physical systems (CPS) in urban management. However, the term IoT and CPS are new in the GIS realm. This article reviews the concepts of IoT and CPS from the perspective of geospatial spaces and proposes the concept of Geo CPS to develop the potential of new technology in the geographic dimension. Two forms of Geo CPS are discussed: pseudo-CPS (PCPS), which projects spatial data onto a display without interaction among data sources, and true-CPS (TCPS), which handles data sources deeply and semantically. While PCPS already has wide industrial applications, TCPS is still in its infancy. The spatial challenge for CPS in geo space involves operating conditions in an open environment, and here, the human-machine system interface will be key. A transformation of our mindset relating to GIS can lead to the creation of new value-added geographical information services. This will require new schemes and platforms for data sharing, processing, security, and privacy, etc.
Keywords: 710; Internet of things (IoT); Space integration; Cyber-physical systems (CPS); Sensing; Processing and Accutation (SPA)